A Review of Different Ideas Concerning the Characteristics of a Good Leader and Shaping New Ideas of an Effective 21st Century Leader - Sereyrath Em (MASI Mandiri Edukasi, 2023)
The current study aims to define a good leader in general, not for any specific companies, schools, offices, or organizations. The author has read and consulted various documents, significantly articles published in reputable outlets, to boost related ideas vis-Ã -vis good leaders from different walks of life. After reading, reviewing, and taking notes, the author focused on different leadership types and the characteristics of good leaders. As a result, a good leader is defined, and suggestions are provided to consider for those who want to become good leaders using just easy ways and simple techniques. In the 21st century, a good leader is someone well-educated and always looks at the past, uses the past as experience, leads what is in the present, and predicts the future so that he can get everything ready and he could solve unforeseen problems. Finally, a comprehensive assessment or investigation could still be made into what makes a sound or effective leader in the 21st century. It is also important to analyze or conduct a comparison of an efficient managerÂ and a good leader. Generally, it is essential to consider how to successfully lead an organization by combining the qualities of a skilled manager and an effective leader.